Evaluating the Effect of Nano-SiO2 on Different Types of Soils: A Multi-Scale Study - Gu, Jiayu; Cai, Xin; Wang, Youqiang; Guo, Dahan; Zeng, Wen (International journal of environmental research and public health, 2022)
A rapid growth in the population leads to a large increase in engineering construction. This means there is an inevitability in regard to building on problematic soils. Soil reinforcement becomes an important subject due to the fact that it is a concern for engineers and scientists. With the development of nanotechnology, more and more nanomaterials are being introduced within the practice of soil reinforcement engineering. In this study, the reinforcing effect of novel nanomaterial nano-silica (SiO2) applied to different kinds of soils was systematically studied. The nano-SiO2-reinforced soil possessed lower final water evaporation loss, and evaporation rates. The nano-SiO2 increased the shear strength of clayey soil and sandy soil under both cured and uncured conditions, but the reinforcing effect on clayey soil was more obvious. The addition of nano-SiO2 promotes the friction angle and cohesion of clayey soil; further, it also increases the cohesion of sandy soil. The unconfined compressive strength of clayey soil was enhanced by nano-SiO2, meanwhile, the nano-SiO2-reinforced soil possessed greater brittleness. The microstructure of nano-SiO2-reinforced soil is shown via SEM analysis, and the results of X-ray diffraction (XRD) tests show that there are no new mineral components generated during the reinforcing process. It was also found that nano-SiO2 possessed little influence on the soil pH value. Adding nano-SiO2 will not damage the original chemical environment of the soil. The microstructure of nano-SiO2-reinforced soil was observed to prove the results above. In general, nano-SiO2 is an excellent soil additive that can improve the mechanical properties of both clayey soil and sandy soil effectively. This research provides more ideas and directions for the purposes of selecting soil reinforcement materials.